2017
DOI: 10.5603/arm.2017.0030
|View full text |Cite
|
Sign up to set email alerts
|

Selected Aspects of Medical Care for Patients with Asthma and Chronic Obstructive Pulmonary Disease (COPD) in Poland

Abstract: Introduction: Noncompliance with healthcare undoubtedly has a strong influence on the high prevalence of uncontrolled obstructive diseases. The aim of our study was to evaluate the quality of medical conduct in patients with asthma or chronic obstructive lung diseases (COPD), with encompassed two-levelled system of health care. Material and methods: A survey of general practitioners (GP), allergists and pulmonologists practicing in Poland was performed between September and December 2016. The basic survey incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…COPD is a disease characterized by airflow limitation, which is strongly associated with increased chronic inflammatory responses to noxious particles or gases (mainly tobacco smoke) in the airways and lungs. Recently, several studies have shown that pulmonary hypertension and pulmonary vascular remodeling are the most important and critical links in the development of COPD in patients with pulmonary heart disease [ 5 , 34 , 35 ]. Therefore, controlling pulmonary vascular remodeling and pulmonary hypertension induced by COPD is important for delaying its cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is a disease characterized by airflow limitation, which is strongly associated with increased chronic inflammatory responses to noxious particles or gases (mainly tobacco smoke) in the airways and lungs. Recently, several studies have shown that pulmonary hypertension and pulmonary vascular remodeling are the most important and critical links in the development of COPD in patients with pulmonary heart disease [ 5 , 34 , 35 ]. Therefore, controlling pulmonary vascular remodeling and pulmonary hypertension induced by COPD is important for delaying its cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Patients having bronchial obstruction due to inflammation in the airways, often present with clinical symptoms such as dyspnea, respiratory restriction, and cough. 1,2 Related studies have shown that there are certain overlaps in the pathogenesis, clinical symptoms, and predisposing factors of asthma and chronic obstructive pulmonary disease. 3 This overlap is referred to as asthma-chronic obstructive pulmonary overlap syndrome (ACOS).…”
Section: Introductionmentioning
confidence: 99%
“…Specialists declared that half of the treatments recommended recently by general practitioners required modifications. The medications were administered via a separate inhaler in most cases [10]. Delayed access to medicines limited their implementation in clinical practice.…”
Section: Introductionmentioning
confidence: 99%